Biologia reprodutiva e seleção dos sítios de nidificação do coleiro-do-brejo (Sporophila collaris) nos campos do sul do Brasil - Rosoni, Jonas Rafael Rodrigues (2017)
In Rio Grande do Sul, are present mosaic of grasslands, among them stands out the Subtropical Field. Among the avifauna described for the state, about 120 species are adapted to live in grasslands, like the little seedeaters. Sporophila collaris has a southern distribution, which inhabits wetland environments. Basic biology works concerning the genus Sporophila seedeaters is growing and adding knowledge from the last decade, however breeding biology data for certain species are still scarce. The aim of this study is present features and information on breeding biology, territory sizes and nest-site selection for the Rusty-collared Seedeaters. The study was conducted in the municipalities of Santa Maria and Manoel Viana. The search of nesting sites and of nests were made during a breeding season (2015/2016) and followed the active search method. Found nests were marked with a ribbon at a distance of 5m, and the breeding territory were georeferenced with GPS. Also, it was defined the length of the breeding season, clutch size, parental care, allowing the calculate of the reproductive success for three methods: apparent, Mayfield and successfully MARK program, recording multiple attempts to renesting and estimating the size of the territories. It was found 52 nests, which 26 in construction, 21 during incubation and 5 in nestling phase. The reproductive period was estimated at 203 days (eight months). Only female builds the nest and incubates the eggs. The incubation period lasts on average 12 days and the nestlings of the length of stay is 11.1 ± 0.78 days in the nest. The clutch were recorded at higher frequency two eggs (54%), followed by three eggs (37%) and one egg (10%) with average size 2.3 ± 0.5 eggs. The care of the prole is biparental, where male and female develop the activities of care, however the females more often than males. The calculated apparent success was 25% (n = 13 nests). The reproductive success calculated by Mayfield method was 13.43% and DSR calculated with the program MARK was 0.947 ± 0.01 (n = 36 nests) generating a probability of survival of 28.9%. Of the 32 pairs found, 23 of them (72%) had at least one nesting record, and nine of them (28%) had at least two nesting attempts. The average size of the territories was 1.46 ± 0.84 ha and the estimated home range was 4.17 ± 2.38 ha. Most pairs, 56% (n = 18) used humid environments as nesting sites, 25% (n = 8) dry conditions and 19% (n = 6) used wetland. However, information about the natural history focused on breeding biology can be useful as tools for the conservation of this group. Thus, we suggest that the Rusty-collared Seedeaters serve as a model for future research in which aid the understanding of reproductive and migratory cycles for genus Sporophila seedeaters, as understand why many species of this genus are so severely affected by the loss and fragmentation of their natural habitats.